Optimal Taxation and Normalisations - Bjørn Sandvik (Center for Economic Studies and ifo Institute (CESifo), 2003)
There still seems to be some confusion about the consequences of normalisations in the optimal taxation literature. We claim that:1) Normalisations do not matter for the real solution of optimal taxation problem.2) Normalisations do matter for good characterisations of the solutions to optimal taxation problems.Whereas the first point is uncontroversial, the second one is less well understood. There is also a need to distinguish between the following senses of taxation of endowment:1) The taxation of own consumption of initial endowments (e.g. leisure).2) The taxation of the sale of initial endowments (e.g. labour).By postponing the normalisation of consumer prices, we detail how normalisations of consumer prices affect the characterisation of optimal commodity taxes, derive the preferred characterisation, and show how it depends on the normalisation. On the way, we discuss the effect of normalisations on measures of the marginal efficiency loss of taxation.
Keywords: 330; optimal taxation; normalisation; marginal cost of public funds